Multicentre cross-sectional study on adverse events and good practices in maternity wards in Brazil and Mexico: same problems, different magnitude - Sousa, Kelienny de Meneses (BMJ Open, 2019)
OBJECTIVE: To evaluate the quality of delivery care in maternity wards in Brazil and Mexico based on good practices (GP) and adverse events (AE), in order to identify priorities for improvement. DESIGN: A multicentre cross-sectional study with data collection from medical records between 2015 and 2016 to compare indicators of maternal and neonatal GP and EA based on the Safe Childbirth Checklist and standardised obstetric quality indicators. Two Brazilian and five Mexican maternity wards participated in the study. Descriptive statistics and χ(2) tests were performed to assess performance and significant differences between the hospitals investigated. SAMPLING: We analysed 720 births in Brazil and 2707 in Mexico, which were selected using a systematic random sampling of 30 medical records every fortnight for 12 2-week periods in Brazil and 18 2-week periods in Mexico. We included women and their newborns, excluding those with congenital malformations. RESULTS: The Mexican hospitals showed greater adherence to GP (58.2%) and a lower incidence of AE (12.9%) than the participating institutions in Brazil (26.8% compliance with GP and 16.0% AE). In spite of these differences, the relative importance of particular quality problems and type of AE are similar in both countries. Tertiary hospitals, caring for women at higher risk, have significantly (p<0.001) higher rates of AE (27.2% in Brazil and 29.6% in Mexico) than institutions attending women at lower risk, where the frequency of AE ranges from 4.7% to 11.2%. Differences were significant (p<0.001) for most indicators of GP and AE. CONCLUSION: Data from outcome and process measures revealed similar types of failures in the quality of childbirth care in both countries and indicate the need of rationalising the use of antibiotics for the mother and episiotomy, encouraging greater adherence to partograph and to the use of magnesium sulfate for the treatment of severe preeclampsia/eclampsia.